Integrated evaluation for advanced removal of nitrate and phosphorus in novel PHBV/ZVI-based biofilters: Insight into functional genes and key enzymes - Jia, Lixia; Sun, Haimeng; Qi Zhou; Dai, Richeng; Wu, Weizhong (JOURNAL OF CLEANER PRODUCTION, 2022)
Effective control of nitrogen and phosphorus simultaneously is of great significance to satisfy the strict requirement of the ecological health of receiving waters. In this study, PHBV/ZVI composites made from solid carbon (poly-3-hydroxybutyrate-cohyroxyvelate, PHBV) and zero-valent iron (ZVI) were proposed to be functional fillers in biofilters for advanced wastewater treatment. Results showed that high-rate treatment performance was obtained with nitrate and phosphorus removal efficiencies of 79-97% and 97-98% in the biofilters packed with PHBV/ZVI composites. Lower N2O and CH4 emission (56.3-129.2 mu g m(-2) h(-1)) were also achieved simultaneously, further indicating the superiority of PHBV/ZVI composites applied in the wastewater treatment. High-throughput quantitative-PCR (HT-qPCR) results uncovered that the existence of ZVI could enrich carbon degradation genes (manA, gam and mxa) and facilitate denitrifier utilize organic matters more efficiently, as evidenced by up-regulations of genes involved in nitrate reduction (nirS and nosZ). Meanwhile, higher Fe concentration and less functional genes inducing lower activities of phosphate metabolism and in PHBV/ZVI systems indicated ZVI corrosion and coprecipitation were the main pathway of phosphorus removal. Network and redundancy analysis highlighted the role of ZVI in the removal of pollutants with keystone genes changed (pox and napA) and genes distribution remodeled compared to single PHBV fillers. Further, the activities of dehydrogenase (DHA) and nitrite reductase (Nir) enzymes also increased by the modulation of microbes, which explicitly interpreted the synergistic promotion of PHBV and ZVI on the denitrification process. These findings provided an alternative for the advanced treatment of wastewater and improve the understanding of C, N and P cycling in the co-occurrence of PHBV and ZVI.